Pengaruh Good Corporate Governance dan Corporate Social Responsibility terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening (Studi Empiris pada Perusahaan Industri Batu Bara yang terdaftar dalam Bursa Efek Indonesia (BEI) Periode 2019-2022) - Gomes, Agata Sarce; Simatupang, Frido Saritua (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study aims to estimate the influence of Good Corporate Governance and Corporate Social Responsibility on Firm Value with Profitability as an intervening variable, by sampling from companies engaged in the coal industry listed on the Indonesia Stock Exchange during 2019-2022 using nonprobability sampling with purposive sampling techniques and data obtained through the official website (BEI) www.idx.co.id. The data analysis method used in this research is path analysis using E-views 10 and the data is confirmed to have passed classical assumptions. The results showed that partially the Independent Board of Commissioners and Corporate Social Responsibility had a positive and significant effect on Earning per Share, but the Audit Committee had no effect on Earning per Share. Then only the Independent Board of Commissioners has a positive and significant effect on Price to Book Value, while the Audit Committee, Corporate Social Responsibility, and Earning per Share do not affect Price to Book Value. And for the mediation results, it is found that Earning per Share fails to mediate the influence of the independent variables (Independent Board of Commissioners, Audit Committee, and Corporate Social Responsibility) on the dependent variable, namely firm value.